PERBEDAAN KADAR ASAM URAT DARAH PUASA DAN TIDAK PUASA PADA MAHASISWA/I PRODI D.IV ANALIS KESEHATAN - Rosnita Sebayang; Desti Amelia (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Fasting is not necessary for uric acid level measurement in most of the medical laboratory. However, theminister of health of Republic Indonesiain 2013regulated that the uric acid measurement should be conductedafter 10-12 hours before the blood sampling, indicating the patient should do fasting before the bloodsampling. The issues of fasting and non-fasting for uric acid test is still in debating until now because severalstudies reported that the most of test result of patients who did not do fasting exhibited a higher uric acidlevel compared to the patients who do fasting. The study uses one group pretest-posttestwhere the mainsubject is divided into two groups which are the fasting group and non-fasting group. The samples of thefasting group have done the fasting activity for 10-12 hours before the blood sampling, while the non-fastingsample spontaneous do the blood sampling without doing any fasting. 34 blood samples are testing on thisstudy.The result indicates that non-fasting students have higher uric acid levels compared to the one whodoes fasting. The statistical analysis using Paired t-test also showed that there is a significant difference inthe uric acid level of fasting and non-fasting samples showed by the significance level (2- tailed) of 0,000which is less than the ? value of 0.005 (Sig.< 0,005) with the confidence level of95%.There is a significantdifference in the uric acid level of fasting and non-fasting samples. The results suggest the patient who wantsto do uric acid measurement doing fasting for 10-12 hours